Anatomy, function, and evolution of jaw and hyobranchial muscles in cryptobranchoid salamander larvae. (18th October 2013) - Kleinteich, Thomas; Herzen, Julia; Beckmann, Felix; Matsui, Masafumi; Haas, Alexander
ABSTRACT Larval salamanders (Lissamphibia: Caudata) are known to be effective suction feeders in their aquatic environments, although they will eventually transform into terrestrial tongue feeding adults during metamorphosis. Early tetrapods may have had a similar biphasic life cycle and this makes larval salamanders a particularly interesting model to study the anatomy, function, development, and evolution of the feeding apparatus in terrestrial vertebrates. Here, we provide a description of the muscles that are involved in the feeding strike in salamander larvae of the Hynobiidae and compare them to larvae of the paedomorphic Cryptobranchidae. We provide a functional and evolutionary interpretation for the observed muscle characters. The cranial muscles in larvae from species of the Hynobiidae and Cryptobranchidae are generally very similar. Most notable are the differences in the presence of the m. hyomandibularis, a muscle that connects the hyobranchial apparatus with the lower jaw. We found this muscle only in Onychodactylus japonicus (Hynobiidae) but not in other hynobiid or cryptobranchid salamanders. Interestingly, the m. hyomandibularis in O. japonicus originates from the ceratobranchial I and not the ceratohyal, and thus exhibits what was previously assumed to be the derived condition. Finally, we applied a biomechanical model to simulate suction feeding in larval salamanders. We provide evidence that a flattened shape of the hyobranchial apparatus in its resting position is beneficial for a fast and successful suction feeding strike. J. Morphol. 275:230–246, 2014. © 2013 Wiley Periodicals, Inc.